Juridical Analysis Of Legal Certainty Of Property Rights To Management Rights In Batam City (Research Study At Batam City Land Office) - Kurnia Wati, Dita; Erniyanti, Erniyanti (UNES Law Review, 2024)
This study aims to determine the Implementation and implementation of Legal Certainty on Property Rights on Management Rights in Batam City (Research study at the Batam City Land Office) and to find out what factors are the obstacles / constraints and solutions to Legal Certainty on Property Rights on Management Rights in Batam City (Research study at the Batam City Land Office). The results of the study explain that the legal arrangements for the issuance of several certificates of property rights in the city of Batam due to errors in interpretation to the application of legislation carried out at that time by the Batam Authority in issuing Decree (SK) Number 734/UM-KPTS/XII/1998 signed by the Chairman of the Batam Authority (OB) at that time. The legal arrangements for the implementation of land ownership rights affirmation of the old kampong community in Batam Island are based on Presidential Instruction No. 2 of 2018 on the Acceleration of Complete Systematic Land Registration in All Regions of the Republic of Indonesia and Regulation of the Minister of Agrarian Spatial Planning/National Land Agency No. 6 of 2018 on Complete Systematic Land Registration. BP Batam in cooperation with the City Government provides land rights status in the form of Property Rights by not recommending the Old Village to be part of BP's Management Rights so that the old village area on Batam Island is under the management of the Batam City Government. The existence of the issued Hak Milik is valid, recognized and applicable in Batam City. Property Rights on land in the area with the status of Management Rights in Batam City have absolutely been released from the supervisory authority of the BP Batam land authority.